Surgery in metastatic prostate cancer: a pilot study. Issue 3 (May 2017) - Sooriakumaran, Prasanna
Abstract : There is some evidence to suggest that radical treatment of the primary tumour in patients diagnosed with metastatic prostate cancer can reduce symptomatic progression and increase survival. In this article, the author describes a pilot study to investigate whether a large study looking at survival benefit in early metastatic disease is feasible in the UK and calls for recruits.